2022
DOI: 10.1371/journal.pntd.0010841
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ knowledge on identification, management and treatment of snakebite cases in rural Malawi: A descriptive study

Abstract: Snakebite envenoming remains a public health threat in many African countries, including Malawi. However, there is a shortage of literature on the knowledge of Health Care Workers (HCWs) and the prevalence of snakebite cases in Malawi. We interviewed HCWs in Neno District to assess their knowledge of snake identification and management of snakebites. We further reviewed patient registers from 2018 to 2021 in all 15 health facilities in the district. We used descriptive statistics to characterize the survey pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
10
1
Order By: Relevance
“…Our results show that most victims seek care from traditional healers and not the formal governmental healthcare system. While this health-seeking behaviour is largely influenced by local factors, this fits well with previous reports [ 7 , 9 , 14 ]. Consequently, healthcare facility-based data on SBE strongly underestimate the true incidence and the sequelae, disabilities and deaths relied on SBE in an area [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show that most victims seek care from traditional healers and not the formal governmental healthcare system. While this health-seeking behaviour is largely influenced by local factors, this fits well with previous reports [ 7 , 9 , 14 ]. Consequently, healthcare facility-based data on SBE strongly underestimate the true incidence and the sequelae, disabilities and deaths relied on SBE in an area [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study was performed in a referral hospital in the capital and is not representative of the situation in Gabon. The true burden of snakebite envenoming is almost certainly underestimated as most snakebites occur in rural areas, and treatment-seeking behaviour of affected individuals, influenced by socioeconomic and cultural factors, leads to a preference for traditional practices so that victims often do not reach the formal healthcare system [ 7 , 8 , 9 ]. Community-based studies on the incidence of snakebites are urgently needed to close the gap in our understanding of the incidence of SBE and provide more accurate estimates to inform policy and guide resource allocation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that THs claimed to be knowledgeable of the snakes found in the area, the seasons with more bites, and very confident regarding the treatment they offer. However, their claims were not scientifically proven compared to HCWs as stated in a previous study in Neno [ 35 ]. The confidence that THs have in their treatment was understood as building trust among the people they served.…”
Section: Discussionmentioning
confidence: 95%
“…The only available study done in the Neno district found knowledge gaps among HCWs regarding snakebite treatment. In addition, HCWs reported that snakebite victims go to THs before reporting to a health facility [ 35 ]. The use of THs in Malawi is common and has been trusted for generations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of medical staff’s professional knowledge and standardized treatment in improving the outcomes of snakebite patients [ 7 ]. A recent global study on the knowledge of medical staff in the diagnosis and treatment of snakebites shows that regardless of the level of development of their respective medical systems, there is a consistent knowledge gap regarding snakebite diagnosis and treatment among medical staff in different countries such as the UK, Cameroon [ 8 ], Nigeria [ 9 , 10 ], Laos [ 11 ], Kenya [ 12 ], Malawi [ 13 ], West African countries [ 14 ], Bhutan [ 15 ], India [ 16 ], etc. Studies have shown that medical staff have obvious deficiencies in the diagnosis and treatment of snakebites.…”
Section: Introductionmentioning
confidence: 99%